Influence of pulse thermal annealing on photoelectrical properties of locally grown polycrystalline silicon films - Mamikonova, V.M.; Kasimov, F.D.; Kemerchev, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The possibility of forming polycrystalline silicon films by pulse thermal annealing has been investigated using measurement of a photo-e.m.f., dark and light voltage-current characteristics. Investigated samples were resistors of rectangular form with the dimensions 400x40 µm² and had contact areas covering 100x100 µm². Ohmic behavior of contacts was ensured by additive diffusion of phosphorus atoms info the film under aluminium electrodes. It is shown that the samples before thermal treatment have utterly symmetrical dark and light voltage-current characteristics, which are essentially changed after samples treatment: at low applied voltages the samples resistance rises more than the order of its magnitude, and a value of a asymmetry coefficient reaches 20. Obtained results have been analyzed from the viewpoint of the model of polycrystalline film conductance taking info account intergranular barriers of the Shottky type. The conclusion is made that optimization of modes of thermal treatment regimes will enable to get rid from electroforming during fabrication of photocells based on such polycrystalline silicon film.